The Effect of Career Development and Work Culture on Employee Performance at the Regional Revenue Agency of Tulang Bawang Regency - Ani, Ani; Parela, Epi (Saburai International Journal of Social Sciences and Development, 2023)
The objectives to be achieved in this study were to determine: 1. the influence of career development on employee performance at the Regional Revenue Agency of Tulang Bawang Regency, 2. the influence of work culture on employee performance at the Regional Revenue Agency of Tulang Bawang Regency, 3. the influence of career development and work culture together on employee performance at the Regional Revenue Agency of Tulang Bawang Regency. The population in this study were employees of the Regional Revenue Agency of Tulang Bawang Regency who became the population in this study. Based on data on the number of Civil Servants (PNS) in the focus of this study were 49 people and saturated samples used in this study. The analytical tools used are validity test, reliability test, normality test, multiple linear regression test and determination coefficient test. The results of the study are: 1. T test results: there is an effect of career development (X1) on employee performance (Y) and there is an effect of work culture (X2) on performance (Y), 2. F test results: there is an effect of career development (X1) and work culture (X2) together affect employee performance (Y).